Va-ka: Igniting the space between Mana Whenua and Mana Moana research relations - Smith, Hinekura; Wolfgramm-Foliaki, ‘Ema (New Zealand Sociology, 2026)
For decades, Māori, the Mana Whenua1 of Aotearoa/New Zealand, have formed powerful research relationships with the decolonising agendas in Hawai‘i and North America. These manaenhancing alliances have forged strong connections, such as supporting language revitalisation in Hawai‘i, the decolonisation of education, as well as land protection struggles on Mauna Kea in Hawai‘i and the Dakota Pipeline protests on the mainland United States. These global research relationships amongst Indigenous peoples have been of critical importance, as we draw on each other’s strengths and determination to effect change and support decolonialisation. However, in doing so Mana Whenua research has often ‘flown over’ our closest Mana Moana relations in the Pacific who, through their own active and critical scholarly engagement, have produced their own transforming research seascape. Igniting the space between Mana Whenua and Mana Moana research alliances offers a crucial and timely return to ancient Moana relationships in the service of transforming our current lived realities. Conceptually, we lash together in this article the Pasifika term vā (relational time and space) with the Māori term ‘kā’ (to ignite, to consider, to be in action) as a theorised methodology that emerges from the language, connections and ways of being which sustain us as both Mana Whenua and Mana Moana. We encourage Māori and Pasifika researchers to come together in purposeful and transformational ways, to pikipiki hama—a Tongan expression meaning ‘lash our canoes together’—to support our common, and differing aspirations for radical change in Higher Education. We support this methodology by sharing our experiences as a Māori researcher and a Tongan researcher working in Higher Education to transform the tertiary land-/seascape for Māori and Pasifika students.